Tuberculosis infection following administration of immune checkpoint inhibitors: a real world observational study - Zhan, Mei; Zhou, Linyan; Liu, Ran; Long, Qinran; Huang, Litao; Xu, Ting; Fu, Yan (Frontiers in Pharmacology, 2025)
BackgroundThis study aims to investigate the incidence of tuberculosis (TB) infection following administration of immune checkpoint inhibitors (ICI) and to explore the risk factors for developing TB in patients treated with ICIs.Research design and methodsWe conducted a retrospective review of patients who had ICI until June 2023. Patient follow-up was extended until death or on July 2025. The primary outcome was the incidence of TB infection in patients treated with ICIs. Logistic regression was used to investigate the associations between clinical characteristics and TB infection after ICI initiation.ResultsOf the 8,199 patients analyzed, 2.65% had a pre-existing TB diagnosis. The incidence of TB following ICI initiation was 1.96%, with pulmonary TB being the most frequent presentation. Logistic regression revealed that pre-existing TB (OR 3.277; [95% CI, 1.822–5.895]; p < 0.001) and male sex (OR 1.798; [95% CI, 1.173–2.756]; p = 0.007) were significantly associated with TB following ICI initiation.ConclusionIn this large, real-world cohort of cancer patients receiving ICI therapy, we observed a notable incidence of tuberculosis. These findings suggest that enhanced clinical vigilance may be warranted for these high-risk populations, and they highlight the need for prospective, controlled studies to definitively quantify the excess TB risk attributable to ICI therapy.Clinical Trial Registrationhttps://www.chictr.org.cn, identifier ChiCTR2300075974.